Nodular scleritis as the eye manifestation in Behcet's syndrome - Damodaran, Karpagam (Oman J Ophthalmol, 2015)
We report a case of a 45-year-old female, who was diagnosed as Behcet's disease and presented to us with nodular scleritis in her right eye.